Pholcid spiders (Araneae: Pholcidae) from northern Vietnam, with descriptions of nineteen new species - Yao, Zhiyuan; Pham, Dinh Sac; Li, Shuqiang (Zootaxa, 2015)
Five genera and 26 species belonging to two subfamilies Arteminae Simon, 1893 (one genus and one species) and Pholcinae C.L. Koch, 1850 (four genera and 25 species) are reported from northern Vietnam, including 19 new species of three genera: Belisana babensis sp. nov. (male, female; Bac Kan), B. cheni sp. nov. (male, female; Bac Kan), B. clavata sp. nov. (male; Ha Giang), B. curva sp. nov. (male; Vinh Phuc), B. decora sp. nov. (male, female; Ninh Binh), B. halongensis sp. nov. (male; Quang Ninh), B. phungae sp. nov. (male, female; Bac Kan), B. pisinna sp. nov. (male; Quang Ninh), B. triangula sp. nov. (male; Phu Tho), B. vietnamensis sp. nov. (male, female; Ninh Binh), B. zhengi sp. nov. (male; Vinh Phuc), Khorata dangi sp. nov. (male; Bac Kan), K. huberi sp. nov. (male, female; Bac Kan), K. protumida sp. nov. (male, female; Quang Binh), Pholcus bifidus sp. nov. (male, female; Quang Binh), P. caecus sp. nov. (male, female; Quang Binh), P. hochiminhi sp. nov. (male, female; Quang Ninh), P. phami sp. nov. (male, female; Bac Kan), and P. zhaoi sp. nov. (male; Ninh Binh). One genus Khorata Huber, 2005 and five species Belisana schwendingeri Huber, 2005, B. sepaku Huber, 2005, Khorata digitata Yao & Li, 2010, Leptopholcus podophthalmus (Simon, 1893), and Pholcus bangfai Huber, 2011 are reported from Vietnam for the first time. Additional new records are given for two species Leptopholcus huongson Huber, 2011 and Physocyclus globosus (Taczanowski, 1874).